Políticas fiscais e efeitos dinâmicos nas economias subnacionais: uma avaliação a partir de modelos de equilíbrio geral aplicados à economia cearense - Paiva, Witalo Lima de (2017)
This thesis aims to evaluate the effects of fiscal policy decisions on the dynamics of the economy of Ceará. To this end, dynamic general equilibrium models calibrated for the local economy are constructed, which consider the economy of Ceará as a small closed economy with a representative family deciding about consumption, leisure and savings, representative firms with production of final goods and local government. There is also the central government that affects the state economy through taxation and the transfer of resources. The models analyze the repercussions of fiscal policy in different contexts by performing specific simulations. The first group of exercises assesses the effects of public investments on the local economy. The study considers permanent and temporary changes in investment, with temporary elevations depicting a scenario in which public consumption expenditures expand due to the operation of the equipment and the built infrastructure. The simulations indicate important and positive effects of public investment on economic growth, consumption and private investment. The exercises demonstrate that temporary increases in investment followed by increases in public consumption lead to a less favorable long-term equilibrium, reinforcing the importance of investments being sustainable. The second group of simulations investigates how the presence of non-Ricardian agents affects the dynamics of the economy of Ceará when there are changes in fiscal policy. In this case, the model explicitly admits the presence of non-Ricardian agents, who present restrictions on access to the credit market. In addition, the model presents versions that consider differential tax treatment and productivity differentials among agents. The results show that the variation of the macroeconomic aggregates does not present significant change, either with the presence or the greater participation of the non-Ricardian agents in the economy. The same is true in the case of differential tax treatment for agents with restricted liquidity. It is only when one considers the productivity differentials between the groups that the economy has a higher rate of growth and reaches a more favorable long-run equilibrium. As for the groups, the response in terms of consumption and labor supply changes when one considers the growing presence of non-Ricardian agents, differential tax treatment and different levels of labor productivity. The third and last set of exercises has as object the new state tax regime implemented by constitutional amendment EC 88/2016. The new fiscal regime limits spending growth, but preserves the implementation of public investments. To evaluate the effects on the dynamics of the economy of Ceará, the model brings variations that simulate different scenarios for government spending. The results indicate that the fiscal adjustment contributes to ensuring the fiscal solidity of the state. The exercises also point to the correction of the state option in preserving public investments, which softens the loss of dynamism due to the fiscal adjustment practiced.